The Didactic Fabric of Folklore: A Narrative Analysis of Values in “Bandha Warisan” - Riandita Riandita; Wiwiek Eko Bindarti; Miss Treesirin Chaloemkiti; Jaraswat Trairat; Shella Dela Cruz (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to systematically identify, describe, and categorize the moral education values ​​contained in the Javanese folktale anthology "Bandha Warisan." The analysis focuses on an in-depth exploration of the implicit and explicit ethical messages in the narrative, as well as its relevance as a source of local wisdom-based teaching materials in the context of character education in Indonesia. Methodology: This research uses descriptive qualitative analysis. Data were collected through careful reading and note-taking techniques from the “Bandha Warisan” anthology. Data validity was ensured through expert judgement (semantic validity) and reliability testing. Main Findings: The analysis identified 31 moral values, systematically categorized into four relational domains: human-God (accepting destiny, prayer, gratitude, repentance) human-others (harmony, mutual aid, respect for parents, cooperation, affection) human-environment (cleanliness, caring for animals); and human-self (honesty, humility, diligence, generosity, keeping promises). These values reflect core Javanese ethical principles such as nrimo, rukun, and andhap asor. Novelty/Originality of this study: This study provides a systematic mapping of moral values from a modern, curated Javanese folktale anthology. It bridges traditional wisdom with contemporary character education, offering a practical reference for educators and parents in using local literature for moral pedagogy. The research highlights the anthology's role as an active instrument for cultural transmission and ethical formation in the modern era.